On atomic and algebraically prime models obtained by closure of definable sets - Yeshkeyev, A.R.; Issayeva, A.K.; Shamatayeva, N.K. (Bulletin of the Karaganda University. Mathematics Series, 2021)
This article discusses the properties of atomic and prime models obtained with the some closure operator given on definable subsets of the semantic model some fixed Jonsson theory. The main result is to obtain the equivalence of the thus defined atomic and prime models, and this coincidence follows the assumption that there is some model with nice-defined properties.